(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
In this paper, microcapsules were produced by complex coacervation using gelatin and acacia as wall materials and olive oil as the core substance. Process parameters, such as the dosage of the crosslinker, concentration of the wall materials, pH Value and the ratio between core and wall materials were analyzed in detail. Moreover, crosslinking degree of wall materials was more important in obtaining good slow release microcapsules. The morphology and particle size distribution of the microcapsules were analyzed by scanning electron microscope and laser particle size analyzer. The oil content and the release rate of the olive oil were also studied. In order to obtain microcapsules with good mobility and dispersal, a spray drying process was used to dry the product. The olive oil microcapsules were obtained with particle size of 3 ∼ 8 μm, and an oil content of about 60%. The optimum process parameters were as follows:dosage of the cross linking agent was 3 ml, the concentration of wall materials was 3%, the pH value of coacervation was 4.0 and the ratio of core/wall material was 1:1. Olive oil microcapsules prepared with these optimal process conditions had good disperse effect and high encapsulation efficiency.